Socioeconomic Aspects of Agroforestry Systems: The Case of Gum-cultivation Cycle (University of Khartoum Journal of Agricultural Sciences, 2025)
The purpose of the study was to attempt to understand thenature of the problems related to production and local marketing ofgum Arabic as seen by producers and local traders. Using structuralquestionnaires and multistage stratified sampling, data were collectedon economic activities, production and productivity, price and pricingpolicy and marketing and trade as well as services provided toproducers. Statistical analysis was carried out using various descriptivemethods including means and means comparisons. The resultsindicated a general declining trend of the areas tapped by households,productivity per unit area, prices received by producers and differentforms of services during the period covered by the study. The level ofthe producer’s price seems to be the most important socioeconomicfactor affecting the decision to produce. The need for institutions thatare more effective and of services that promote production andmarketing were seen as essential. The results have importantimplications on pricing policies and sustainability of the gum-cultivation cycle as an integrated management system in the gum beltof the Sudan.
Keywords: Gum Arabic belt; cultivation cycle; perception; policies